Russian gas exports to Europe: unravelling the misconceptions - Stern, J; Yafimava, K (Oxford Institute for Energy Studies, 2014)
Russian gas exports to Europe, and Soviet exports before them, have been controversial since they started, in the late 1960s. As the largest single component of European gas supply, they are the subject of ongoing security and geopolitical controversies. However, much of the commentary on these controversies is subject to misconceptions which, in the 2010s, have been compounded by growing regulatory complexities, particularly in relation to pipeline infrastructure.